2023
DOI: 10.1002/jsfa.12720
|View full text |Cite
|
Sign up to set email alerts
|

Composition, functional properties and safety of honey: a review

Abstract: Honey has been used not only as a food source but also for medicinal purposes. Recent studies have indicated that honey exhibits antioxidant, hepatoprotective, hypolipidemic, hypoglycemic and anti‐obesity properties, as well as anticancer, anti‐atherosclerotic, hypotensive, neuroprotective and immunomodulatory activities. These health benefits of honey could be attributed to its wide range of nutritional components, including polysaccharides and polyphenols, which have been proven to possess various beneficial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 129 publications
1
11
0
Order By: Relevance
“…), which makes it viscous, as well as enzymes, mineral salts, vitamins, and trace elements. 40 Thus, the analysis of honey contaminants is impossible without sample preparation. Previously, for the detection of the antibiotics neomycin, tylosin, and lincomycin, we applied a sample preparation technique based on the extraction of these compounds from honey with ethyl acetate, centrifugation of the extracts, and evaporation of the organic phase.…”
Section: Resultsmentioning
confidence: 99%
“…), which makes it viscous, as well as enzymes, mineral salts, vitamins, and trace elements. 40 Thus, the analysis of honey contaminants is impossible without sample preparation. Previously, for the detection of the antibiotics neomycin, tylosin, and lincomycin, we applied a sample preparation technique based on the extraction of these compounds from honey with ethyl acetate, centrifugation of the extracts, and evaporation of the organic phase.…”
Section: Resultsmentioning
confidence: 99%
“…Honey is a natural sweetener with various health benefits, including hepatoprotective, antioxidant, anti-obesity, hypolipidemic, and hypoglycemic properties. Honey also has anti-atherosclerotic, anti-cancer, hypotensive, immunomodulatory and neuroprotective effects ( 5 ). In addition, honey has a greater sweetening power than sugar, so it can partially or totally replace the use of sugar in confectionery products.…”
Section: Introductionmentioning
confidence: 99%
“…Honey is a natural, sweet and flavorful product used since ancient times in different countries due to its functional and therapeutic effects [1]. This bee product contains more than 200 natural substances, mostly composed of sugar and other minor components including organic acids, proteins, enzymes, amino acids, volatile compounds, minerals, flavonoids and phenolic acids [2].…”
Section: Introductionmentioning
confidence: 99%
“…In view of the increasing risk factors to humans for various fatal diseases, there is a global trend towards the study of therapeutic antioxidants. It has been reported that there is an inverse relationship between the dietary intake of antioxidant-rich food and medicinal plants and the incidence of human diseases [1,14]. Many antioxidant compounds naturally occurring in plant sources have been identified as free radical or active oxygen scavengers [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation